2019
DOI: 10.1126/science.aay1436
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial light response reveals an orphan desaturase for human plasmalogen synthesis

Abstract: Plasmalogens are glycerophospholipids with a hallmark sn-1 vinyl ether bond. These lipids are found in animals and some bacteria and have proposed membrane organization, signaling, and antioxidant roles. We discovered the plasmanylethanolamine desaturase activity that is essential for vinyl ether bond formation in a bacterial enzyme, CarF, which is a homolog of the human enzyme TMEM189. CarF mediates light-induced carotenogenesis in Myxococcus xanthus, and plasmalogens participate in sensing photooxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(128 citation statements)
references
References 40 publications
(51 reference statements)
1
125
0
Order By: Relevance
“…Among them, plasmanyl desaturase (1′-alkyl desaturase) is a predicted unstable membrane enzyme that remains to be identified for many years. In a recent report, the enzyme CarF found in an aerobic bacterium Myxobacteria was confirmed to be the 1′-alkyl desaturase for the last step of plasmalogen formation ( Gallego-García et al, 2019 ). Its homolog TMEM189 was successively identified in mice and human ( Gallego-García et al, 2019 ; Werner et al, 2020 ).…”
Section: The Oxygen-dependent Pathway Of Plasmalogens Biosynthesismentioning
confidence: 97%
See 3 more Smart Citations
“…Among them, plasmanyl desaturase (1′-alkyl desaturase) is a predicted unstable membrane enzyme that remains to be identified for many years. In a recent report, the enzyme CarF found in an aerobic bacterium Myxobacteria was confirmed to be the 1′-alkyl desaturase for the last step of plasmalogen formation ( Gallego-García et al, 2019 ). Its homolog TMEM189 was successively identified in mice and human ( Gallego-García et al, 2019 ; Werner et al, 2020 ).…”
Section: The Oxygen-dependent Pathway Of Plasmalogens Biosynthesismentioning
confidence: 97%
“…In a recent report, the enzyme CarF found in an aerobic bacterium Myxobacteria was confirmed to be the 1′-alkyl desaturase for the last step of plasmalogen formation ( Gallego-García et al, 2019 ). Its homolog TMEM189 was successively identified in mice and human ( Gallego-García et al, 2019 ; Werner et al, 2020 ). Knock out of the animal homolog in human cell lines resulted in the deficiency of plasmalogens, indicating that TMEM189 is needed to catalyze the final step in plasmalogen synthesis in human cells ( Gallego-García et al, 2019 ).…”
Section: The Oxygen-dependent Pathway Of Plasmalogens Biosynthesismentioning
confidence: 97%
See 2 more Smart Citations
“…Note Added in Proof. A recent study characterizing a bacterial light response also found that the TMEM189 gene encodes PEDS (44).…”
Section: Harvest Of Mouse Tissues For Analysis Of Peds Activity and Pmentioning
confidence: 95%